Smad4 Deficiency Promotes Pancreatic Cancer Immunogenicity by Activating the Cancer‐Autonomous DNA‐Sensing Signaling Axis. Issue 7 (22nd January 2022) - Xiong, Wenjing; He, Wenzhuo; Wang, Tiantian; He, Shuai; Xu, Feifei; Wang, Zining; Wang, Xiaojuan; Guo, Hui; Ling, Jianhua; Zhang, Huanling; Liu, Yongxiang; Xing, Kaili; et al.
Abstract: Smad4, a key mediator of the transforming growth factor‐ β signaling, is mutated or deleted in 20% of pancreatic ductal adenocarcinoma (PDAC) cancers and significantly affects cancer development. However, the effect of Smad4 loss on the immunogenicity and tumor immune microenvironment of PDAC is still unclear. Here, a surprising function of Smad4 in suppressing mouse PDAC tumor immunogenicity is identified. Although Smad4 deletion in tumor cells enhances proliferation in vitro, the in vivo growth of Smad4 ‐deficient PDAC tumor is significantly inhibited on immunocompetent C57BL/6 (B6) mice, but not on immunodeficient mice or CD8 + cell‐depleted B6 mice. Mechanistically, Smad4 deficiency significantly increases tumor cell immunogenicity by promoting spontaneous DNA damage and stimulating STING‐mediated type I interferon signaling, which contributes to the activation of type 1 conventional dendritic cells (cDC1) and subsequent CD8 + T cells for tumor control. Furthermore, retarded tumor growth of Smad4‐deficient PDAC cells on B6 mice is largely reversed when Sting is codeleted, or when the cells are implanted into interferon‐alpha receptor‐deficientmice or cDC1‐deficientmice. Accordingly, Smad4 deficiency promotes PDAC immunogenicity by inducing tumor‐intrinsic DNA damage‐elicited type I interferon signaling. Abstract : The author's findings establish that the commonly inactivated tumor suppressor Smad4 is a critical regulator of pancreatic ductal adenocarcinoma tumor immunogenicity by activating cancer‐autonomous DNA sensing signaling, and suggest a potential role of Smad4 expression as a biomarker in developing future effective immunotherapy for PDACs.